Margoculture : a Vital Component for Plant Health in Future - Jattan, S. S.; Kumar, Shashi; Pujar, G. (Indian Forester, 1995)
Margoculture is a vital component for plant health since neem gives us a cleaner ecosystem with biodegradable environment friendly biopesticides. Fruit production oriented management promises better monetary returns. Its improved yield can be obtained by selection, vegetative propagation and inoculation of VAM.